Impact of digital integrated health platforms on diabetes management: evidence from Tianjin, China - Zhaoqi Xu; Xiaoyu Xi; Ennan Wang (BMC Health Services Research)
Abstract Objective Evaluate the impact of digital integrated health platforms on diabetes patients' health in Tianjin. Method Analyzed data from 2,883 patients under Tianjin’s digital integrated health platform using descriptive statistics and Probit regression. Results Chronic disease management significantly reduced fasting glucose by 1.68%, postprandial glucose by 3.4%, and HbA1c by 0.45%. High-compliance patients experienced greater reductions, including a 5.55% decrease in fasting glucose. Conclusion Digital health platforms effectively improve glycemic control, especially with high patient compliance, supporting their broader implementation in chronic disease management.